Study on the Dispersion Law of Typical Pollutants in Winter by Complex Geographic Environment Based on the Coupling of GIS and CFD—A Case Study of the Urumqi Region - Jianzhou Jiang; Afang Jin (Applied Sciences)
Urumqi is located at the northern foot of the Tianshan Mountains. Its topographical features have a significant impact on the transport and dispersion of air pollutants. Moreover, its winter is extremely long, lasting up to six months. A combination of an irrational energy consumption structure, unique meteorological conditions, and complex geographical terrains has led to a substantial increase in NO2 emissions, severely damaging the local ecological environment. In this study, we integrate Geographic Information System (GIS) and Computational Fluid Dynamics (CFD). By leveraging GIS’s powerful spatial analysis capabilities and CFD’s high-precision fluid simulation technology, we significantly enhance the simulation accuracy of complex phenomena like airflow and pollutant diffusion. Additionally, the inverse distance weighted interpolation method is comprehensively employed to analyze the Air Quality Indices (AQIs) of typical pollutants in different districts of Urumqi during winter. The results reveal that high altitude causes instability of the dominant near-surface winds within the atmospheric boundary layer. The increasing frequency of surface calm winds reduces the advective transport of atmospheric pollutants. Topography and winter meteorological conditions are identified as the primary factors contributing to pollutant accumulation. This research not only unveils the fundamental mechanisms of pollutant dispersion in mountainous terrains but also validates the practicality of coupling GIS and CFD, providing a theoretical basis for pollution dispersion studies in this region. This study reveals the general laws of pollutant dispersion in mountainous terrain, resolves the issue of establishing complex geographical models, and demonstrates the feasibility of coupling the GIS and CFD. Meanwhile, it provides a theoretical basis for pollution dispersion in this region.